Coupled continuous–discrete formulation based on microplane and strong discontinuity models for representing non-orthogonal intersecting cracks. (15th March 2021) - Kakarla, Santosh; Rastiello, Giuseppe; Richard, Benjamin; Giry, Cédric
Abstract: Fracture processes in quasi-brittle materials are governed by the strain localization phenomenon, which involves the formation of localized damage zones and cohesive cracks. In this work, we present numerical tools to model strain localization from the onset of localized damage to the formation and propagation of multiple intersecting cracks. Two main ingredients are used for this purpose: (i) a microplane model to describe the initial anisotropic damage phase; (ii) the strong discontinuity method to introduce cracks as strong discontinuities in the damaged continuum using the Embedded Finite Element Method (E-FEM). Here, we formulate the microplane microdamage model within a thermodynamic framework by means of simple constitutive laws on each microplane. In order to describe intersecting cracks, we extend the standard E-FEM to accommodate two strong discontinuities. The coupling between the microplane microdamage model with the strong discontinuity model is achieved using a transition method based on the energy equivalence between both models. Exploiting the anisotropic description provided by the microplane model, transition criteria are formulated based on the quantities defined on each microplane. The proposed methodologies are illustrated using several elementary test cases involving both simple and complex stress-strain states. Highlights: A model to describe non-orthogonal intersecting cracks is proposed. It is based on a coupling between microplane and E-FEM approaches. Numerical implementation is detailed thoroughly. Representative case studies are exposed and discussed.